SECRE-MEN: A Lightweight Quantum-Resilient Authentication Framework for IoT-Edge Networks - Faleh, May Adnan; Abdulsada, Ali M.; Alaidany, Ali A.; Al-Shareeda‬‏, ‪Mahmood A.; Almaiah, Mohammed Amin; Shehab, Rami (Journal of Robotics and Control (JRC), 2025)
The wide 6G-IoT and Mobile Edge Computing (MEC) deployments give rise to severe concerns in authentication, revocation and protection against quantum-post and side channel attacks. In this paper, SECRE-MEN (Secure and Efficient Cryptographic Revocable Authentication for MEC enabled Networks) is presented to be a lightweight and scalable authentication architecture specifically designed for the resource limited IoT systems. SECRE-MEN consists of three main parts: (1) Masked Cryptographic Techniques that are used to randomise elliptic curve operations, thereby mitigate side-channel attacks, (2) VCs, providing support for digitally-signed, lightweight authentication, without requiring the use of bulky certificates, and (3) a Bloom filter-based RDB, which is distributed across multiple MEC nodes, to allow for fast, memory-efficient revocation checks. To enable future-proof security post-quantum cryptography (PQC) is included in SECRE-MEN by lattice-based schemes, such as Kyber and Dilithium, which may incur additional computational cost on ultra-low-power platforms according to the trade-off introduced in this paper. Effort experiments show that the proposed RAM-MENAMI decreases 29.3% the computation cost, and reduces 21.8% the communication budget and improve 20.3% of power efficiency in comparison with the RAM-MEN. In addition, SECRE-MEN is resistant against impersonation, MITM, replay and quantum attacks, as well as allows for dynamic revocation and secure synchronization among MEC nodes. This places SECREMEN as an effective toolkit for cybersecurity of massive IoT-MEC networks in the era of the evolving 6G.